2020
DOI: 10.1021/acscatal.0c00472
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Control in Tandem Catalytic Furfural Upgrading on Zeolite-Encapsulated Pt Nanoparticles through Site and Solvent Engineering

Abstract: Selectivity control is a pressing challenge in developing selective tandem catalytic processes. In this work, we demonstrate that tailoring types of acid sites of zeolite-encapsulated Pt nanoparticles (NPs) and choosing solvents provide a compelling strategy to manipulate product distribution in tandem catalysis. The model tandem furfural conversion with acetone and ethanol (EtOH) is investigated in cyclohexane and EtOH solvents. Pt NPs encapsulated in ZSM-5 with Brønsted acid sites (BAS) only located in intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 62 publications
5
40
0
Order By: Relevance
“…In the further work, Xu's group ulteriorly investigated the influences of the nature and density of acid sites in ZSM-5-encapsulated Pt NP catalysts (Pt@ZSM-5) on the product distribution in a tandem catalytic upgrade of furfural (Figure 18f). [185] The Pt@Na-ZSM-5 catalyst was also synthesized by the cationic polymer-assisted method and followed by completely exchanging of Na + with H + to obtain a H-type Pt@H-ZSM-5. The solidstate NMR and spectroscopy experiments confirmed that the Pt@H-ZSM-5 has both distinct Lewis acid sites and Brønsted acid sites (Figure 18h), while the Pt@Na-ZSM-5 only possesses the former (Figure 18f).…”
Section: Construction Of Multifunctional Sites For Cascade Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the further work, Xu's group ulteriorly investigated the influences of the nature and density of acid sites in ZSM-5-encapsulated Pt NP catalysts (Pt@ZSM-5) on the product distribution in a tandem catalytic upgrade of furfural (Figure 18f). [185] The Pt@Na-ZSM-5 catalyst was also synthesized by the cationic polymer-assisted method and followed by completely exchanging of Na + with H + to obtain a H-type Pt@H-ZSM-5. The solidstate NMR and spectroscopy experiments confirmed that the Pt@H-ZSM-5 has both distinct Lewis acid sites and Brønsted acid sites (Figure 18h), while the Pt@Na-ZSM-5 only possesses the former (Figure 18f).…”
Section: Construction Of Multifunctional Sites For Cascade Reactionsmentioning
confidence: 99%
“…i,j) Product distribution in the conversion of furfural on i) Pt@Na-ZSM-5 and j) Pt@H-ZSM-5. Reproduced with permission [185]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%
“…The overexploitation and depletion of non-renewable fossil source are causing aggravating energy crisis and severe environmental pollution [1][2][3][4]. Upgrading of various renewable biomassderived platform chemicals is a sustainable approach to provide valuable biofuels and high value-added chemicals for human society [5][6][7][8]. Furfural (FAL) is a crucial versatile intermediate to manufacture biofuels and high value products, which was directly obtained from enormous potential supply of lignocellulose [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] The main barrier could be that the selective transformation of FF into GVL requires multiple steps (Scheme 1), including hydrogenation, hydrolysis ring-opening, partial hydrogenation, cyclization, and other steps (e.g., etherication, esterication, and lactonization), in which a specic active site is needed for each step of the reaction. 9,24,25 In addition, the reaction process is oen accompanied by the formation of humin, [26][27][28] making it far from ideal for commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…33 In addition, the Brønsted acid site is also essential for the ring-opening reaction. 31 In the reported studies, the non-noble metals that catalyze the cascade transformation of FF into GVL are mostly Zr-based catalysts, [26][27][28] while there are few reports on Hf-based catalysts. 30 Although these prepared catalysts show good catalytic activity for the conversion of FF to GVL, they have some disadvantages too that cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%